2016
DOI: 10.18805/ijare.v0iof.3757
|View full text |Cite
|
Sign up to set email alerts
|

Management of rhizome rot disease of ginger using eco-friendly natural products

Abstract: Rhizome rot caused by Pythium spp and Fusarium spp is one of the most devastating diseases of ginger in most of the ginger growing areas of the Nepal. Realizing the context for development of alternative control strategies to reduce dependency on synthetic fungicides, a field experiment on management of rhizome rot disease of ginger using eco-friendly natural products was conducted at GRP, Kapurkot, Salyan during 2012/2013. Fresh and fermented extract of Artemesia vulgaris Linn (Titepati), Urtica dioica (Sisno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…Turmeric rhizome yields were found significantly highest (42.71 t•ha -1 ) in the treatment applying vermicompost along with synthetic fertilizers in southern India (Isaac & Varghese 2016). Similarly, some studies found that various Trichoderma species are effective to manage rhizome rot disease in ginger and turmeric (Bharathi & Sudhakar 2011;Acharya et al 2016;Thakur et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Turmeric rhizome yields were found significantly highest (42.71 t•ha -1 ) in the treatment applying vermicompost along with synthetic fertilizers in southern India (Isaac & Varghese 2016). Similarly, some studies found that various Trichoderma species are effective to manage rhizome rot disease in ginger and turmeric (Bharathi & Sudhakar 2011;Acharya et al 2016;Thakur et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“… Fusarium oxysoprum f. sp. zingiberi Pythium aphanidermatum [ 91 ] Acorus calamus Allamanda cathertica Lasia spinosa Laurus nobilis Pythium aphanidermatum [ 92 ] Alamonda leaf extract Fusarium oxysporum [ 93 ] Artocarpus lakoocha Hemedesmus indicus Elaegnus kologa Schlecht Polyalthia longifolia Croton roxburghii Balak. P. aphanidermatum F. oxysporum [ 94 ] …”
Section: Management Of Soft Rot Of Gingerunclassified
“…Additionally, Neem leaves were found to have certain sulfurous substances that had fungicidal capabilities, according to Pant et al [ 90 ]. Acharya et al [ 91 ] reported the activity of various plant extracts such as Arthemesia vulgaris Linn, Urtica dioica, Nicotiana tabacum, and Capsicum annuum Linn against Pythium and Fusarium species that cause soft rot of ginger. In another study, Kumar et al [ 92 ] demonstrated the antifungal activity of extracts of Acorus calamus, Allamanda cathertica, Lasia spinosa, and Laurus nobilis against Pythium aphanidermatum that causes ginger soft rot disease.…”
Section: Management Of Soft Rot Of Gingermentioning
confidence: 99%
“…Patogen dapat menyerang tanaman rimpang, baik di persemaian maupun di lahan pertanian, yang dapat menyebabkan kematian rimpang dan tanaman. Penyakit rimpang dapat menurunkan produksi jahe dan menurunkan hasil panen sebesar 50% hingga 90% (Acharya, et al, 2016). Pengembangan budidaya jahe merah untuk memenuhi kebutuhan industri biofarmasi memerlukan metode biologis untuk mengendalikan penyakit tanaman (Marwan, et al, 2023).…”
Section: Pendahuluanunclassified